FORMATIVE ASSESSMENT IN L2 CLASSROOM IN CHINA: THE CURRENT SITUATION, PREDICAMENT AND FUTURE - Jian, Huang; Luo, Shaoqian (Indonesian Journal of Applied Linguistics, 2014)
Abstract: With the reform of English education in China since 2001, formative assessment (FA) has found its way into the key educational policy documents such as National English Curriculum Standards for Basic Education (NECS for BE) (MoE, 2001 2011), National English Curriculum Standards for Senior High School (NECS for SHS) (MoE, 2003) and College English Curriculum Requirements (CECR) (MoE, 2004 2007) and therefore aroused the interests from both researchers and teachers. To understand FA development in China over the past 12 years, a synthesis study was conducted to analyze the current situation and predicament of FA in China based on the published FA articles in Chinese journals and educational newspapers from 2001 to 2012 and the published FA monographs and unpublished Ph.D.dissertations collected from various sources so far. The study shows FA is inadequately researched, poorly understood and improperly implemented in China. It is believed that the predicament of FA may be attributable to a variety of factors such as inadequate financial support, lack of quality research into various aspects of FA, imbalance of quality research focus, limited knowledge of the latest developments of FA, the shortage of L2-related FA research, the tension between FA and Summative Assessment (SA) in the dominant testing culture of China, the time-consuming nature of FA and lack of professional FA training. To solve these problems, by drawing on the local context and international experiences, this paper puts forward the following suggestions: (1) More financial investment supporting balanced quality research into important issues of FA; (2) Clarification of FA concept; (3)Study of FA in relation to underlying L2theories; (4)Promotion of student SA performance throughFA; (5) Development of ready-to-use FA; and (6) Strengthening professional development for FA. The context-based proposal for FA could provide a reference for other contexts similar to China, especially the Asian countries in terms of economical development and/or educational culture.Â Key words: formative assessment in China, context-based proposal, FA researchÂ